基于EDEM的单轴螺旋榨油机工况分析与参数优化Working condition analysis and parameter optimization of single stage screw press based on EDEM - 欧阳锐凌1，2，董霖1，任洋1，2，李平1，2，雷元1，2，王霜1，冉龙勇3，王清松3 OUYANG Ruiling1，2，DONG Lin1，REN Yang1，2，LI Ping1，2，LEI Yuan1，2， WANG Shuang1，RAN Longyong3，WANG Qingsong3 (Zhongguo youzhi, 2022)
为了提高螺旋榨油机的日处理量，利用EDEM软件对6YL-76型单轴螺旋榨油机传输挤压段的工作过程进行仿真分析，以油菜籽-油液混合物颗粒群沿榨螺径向的合成速度波动幅度来表征颗粒的混合搅拌效果，并以合成速度波动幅度和日处理量为指标，对榨螺深度和榨圈圆弧半径进行了两因素三水平全面试验，建立了榨螺深度、榨圈圆弧半径与日处理量的回归模型并进行参数寻优，综合考虑合成速度波动幅度和日处理量得到最优值。结果表明：运用仿真试验对于研究螺旋榨油机内部工况具有优越性；螺旋榨油机日处理量随榨螺深度和榨圈圆弧半径增大有不同程度的提高；油菜籽-油液混合物颗粒合成速度波动幅度由榨螺深度主导；榨螺深度和榨圈圆弧半径的最优组合为榨螺深度12 mm，榨圈圆弧半径 6 mm。在优化条件下，6YL-76型单轴螺旋榨油机的日处理量提高了18.26%，其工作性能得到较大幅度提升。 In order to improve the daily processing capacity of the screw press, EDEM software was used to simulate the working process of the transmission extrusion section of 6YL-76 single stage screw press. The mixing and stirring effect of the particles was characterized by the fluctuation amplitude of the synthetic speed of the rapeseed-oil mixture particles group along the radial direction of the screw. The fluctuation amplitude of the synthetic speed and the daily processing capacity were taken as indicators, a two-factor, three-level comprehensive test was carried out on the worm depth and the circular arc radius of the pressure ring, and the regression model between the worm depth, the circular arc radius of the pressure ring and the daily processing capacity was established and optimized to obtain the optimal value by taking into account the fluctuation amplitude of the synthetic speed and the daily processing capacity. The results showed that the simulation test had advantages for studying the internal working conditions of the screw press；the daily processing capacity of the screw press increased with the increase of the worm depth and the circular arc radius of the pressure ring; the fluctuation amplitude of synthesis rate of rapeseed-oil mixture particles was dominated by the worm depth; the optimal combination of worm depth and circular arc radius of the pressure ring was 12 mm and 6 mm, respectively.Under the optimal conditions, the daily processing capacity of the 6YL-76 single stage screw press increased by 18.26% and its working performance was improved more significantly.